Media and Press in Legal Perspective: Protecting Rights and Responsibilities in the Digital Age - Riyanto, Mochamad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The digital age has brought significant changes in the media and press landscape, shifting the dominance of traditional media towards more dynamic digital platforms. This article aims to analyze legal protection for the media in Indonesia, identify challenges of the digital era, and explore solutions to balance press freedom and legal responsibility. Using a normative juridical approach, this research utilizes primary data from laws and regulations, such as the Press Law and ITE Law, as well as secondary data from related literature. The results show that although press freedom has been guaranteed through various regulations, its implementation still faces obstacles, including censorship, the spread of hoaxes, and media commercialization. In addition, the multiple interpretations of several articles in the ITE Law often become loopholes to limit legitimate criticism. This article highlights the importance of legal reform through regulatory updates, strengthening oversight institutions such as the Press Council, and improving people's digital literacy. The article concludes that the balance between press freedom and legal responsibility can only be achieved through a holistic approach that includes legal substance, institutional structure, and a supportive legal culture. This reform is expected to create a healthy, accountable, and democracy-supporting media ecosystem.